Comparison of efficacy of azithromycin vs. doxycycline in the treatment of acne vulgaris - (:unkn) unknown (BLACKWELL PUBLISHING LTD, 2005)
Acne vulgaris is a common inflammatory disorder of the skin. Oral antibiotics are known to be effective in its treatment. A randomized, investigator-blinded study was performed to compare the efficacy of azithromycin with doxycycline. Fifty-one patients were randomized to receive either azithromycin 500 mg/day on 3 consecutive days per week in the first, on 2 consecutive days per week in the second, and on 1 day per week in the third month. The other group was given doxycycline twice a day for the first month and once a day for the second and third months. Clinical assessment was made at baseline, at the end of first, second, third, and post-treatment first and second months. Side effects were recorded. Statistically significant improvement for the facial lesions were obtained with both drugs. Neither drug was shown to be more effective than the other. The beneficial effect continued until 2 months after treatment. In the azithromycin group three patients had diarrohea, while photosensitivity was seen in two patients using doxycycline. This study indicates that azithromycin is at least as effective as doxycycline in the treatment of acne.
Keywords: RESISTANT PROPIONIBACTERIA; STREPTOCOCCUS-PNEUMONIAE; ERYTHROMYCIN; PATHOGENESIS; MACROLIDES